2017
DOI: 10.1038/onc.2017.296
|View full text |Cite
|
Sign up to set email alerts
|

Berberine binds RXRα to suppress β-catenin signaling in colon cancer cells

Abstract: Berberine, an isoquinoline alkaloid, is a traditional oriental medicine used to treat diarrhea and gastroenteritis. Recently, we reported that it could inhibit the growth of intestinal polyp in animals and in patients with the familial adenomatous polyposis by downregulating β-catenin signaling. However, the intracellular target mediating the effects of berberine remains elusive. Here, we provide evidence that berberine inhibits β-catenin function via directly binding to a unique region comprising residues Gln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 56 publications
(78 reference statements)
3
109
1
Order By: Relevance
“…Berberine is a phytochemical compound isolated from numerous types of medicinal plants and exhibits antitumor properties against various malignancies (14,30). Berberine inhibited the growth of a human colon carcinoma xenograft in nude mice via exhibiting an inhibitory effect on the proliferation of colon cancer cells by binding retinoid X receptor-α to suppress β-catenin signaling (17). In breast cancer, berberine inhibited the growth and migration of breast cancer cells via binding to vasodilator-stimulated phosphoprotein (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berberine is a phytochemical compound isolated from numerous types of medicinal plants and exhibits antitumor properties against various malignancies (14,30). Berberine inhibited the growth of a human colon carcinoma xenograft in nude mice via exhibiting an inhibitory effect on the proliferation of colon cancer cells by binding retinoid X receptor-α to suppress β-catenin signaling (17). In breast cancer, berberine inhibited the growth and migration of breast cancer cells via binding to vasodilator-stimulated phosphoprotein (31).…”
Section: Discussionmentioning
confidence: 99%
“…It is traditionally used as an antibiotic to treat Berberine, a natural plant alkaloid, synergistically sensitizes human liver cancer cells to sorafenib dysentery, gastrointestinal diseases and diarrhea in China, and is a relatively cheap compound (14,15). Previous studies have reported that berberine exerts an anticancer activity in multiple types of cancer and inhibits the proliferation of cancer cells by inducing apoptosis (16)(17)(18)(19). The possible molecular mechanism of the effect of berberine involves its interaction with numerous molecular targets, including transcription factors, cytokines, enzymes, receptors, oncomiRs and tumor-suppressive miRs (20).…”
Section: Introductionmentioning
confidence: 99%
“…BBR is one of the commonly used drugs in the treatment of intestinal infections in China [6]. In addition to its broad spectrum bacteriostatic effects [7][8][9], BBR is reported to have anti-inflammatory, anti-oxidant, anti-tumor, hypoglycemic and anti-cardiac arrhythmia qualities [10][11][12][13][14]. Studies also reported that BBR had good bacteriostatic effect on E. coli and Bacillus subtilis [15].…”
Section: Berberine (Bbr) Is the Main Component Of The Traditional Chimentioning
confidence: 99%
“…Moreover, apigenin also restrains βcatenin nuclear translocation in HCT15 cells and SW480 cells activated by LiCl in a concentration-dependent manner [64]. However, unlike ursolic acid, berberine is an isoquinoline alkaline from Coptis chinensis and demonstrates inhibitory effect on the expression, instead of the degradation of β-catenin in HCT116 cells [65]. Likewise, tetrandrine, an alkaloid bis-benzylisoquinoline isolated from the dried root of Stephania tetrandra S. Moore, confers resistance to proliferation and apoptosis in colon cancer via downregulating IGF binding protein 5 expression, which promotes β-catenin degradation and downregulates c-Myc expression in dimethylhydrazine-and dextran sodium sulphateinduced colorectal cancer LoVo cells [66].…”
Section: Colon Cancermentioning
confidence: 99%